Development of caecaloids to study host–pathogen interactions: new insights into immunoregulatory functions of Trichuris muris extracellular vesicles in the caecum. Issue 9 (August 2020) - Duque-Correa, María A.; Schreiber, Fernanda; Rodgers, Faye H.; Goulding, David; Forrest, Sally; White, Ruby; Buck, Amy; Grencis, Richard K.; Berriman, Matthew
Graphical abstract: Highlights: Development of new methods to generate, culture and characterise mouse caecaloids is described. Caecaloids recapitulate the caecal epithelium composition and spatial organisation. Caecaloids can be used to study host–caecal pathogen interactions in vitro. Trichuris muris EVs exert novel immunoregulatory effects on intestinal epithelial cells. Abstract: The caecum, an intestinal appendage in the junction of the small and large intestines, displays a unique epithelium that serves as an exclusive niche for a range of pathogens including whipworms ( Trichuris spp.). While protocols to grow organoids from small intestine (enteroids) and colon (colonoids) exist, the conditions to culture organoids from the caecum have yet to be described. Here, we report methods to grow, differentiate and characterise mouse adult stem cell-derived caecal organoids, termed caecaloids. We compare the cellular composition of caecaloids with that of enteroids, identifying differences in intestinal epithelial cell populations that mimic those found in the caecum and small intestine. The remarkable similarity in the intestinal epithelial cell composition and spatial conformation of caecaloids and their tissue of origin enables their use as an in vitro model to study host interactions with important caecal pathogens. Thus, exploiting this system, we investigated the responses of caecal intestinal epithelial cells to extracellular vesicles secreted/excreted by the intracellular helminth Trichuris muris. Our findings reveal novel immunoregulatory effects of whipworm extracellular vesicles on the caecal epithelium, including the downregulation of responses to nucleic acid recognition and type-I interferon signalling.